Prevalence of childhood obesity in Portugal: a narrative review of the literature - Frade,Fátima (2020)
Abstract Background: The number of childhood obesity cases has been increasing in several countries around the world. In view of all the associated complications at an early stage of child development, it becomes urgent to understand this problem in depth. Objective: The aim of this work was to describe the prevalence of childhood obesity in Portugal and analyze the trend of its evolution in recent years. Materials and Methods: This is a narrative review of the literature in the databases on the following platforms: Academic Google, Scientific Electronic Library Online (SciELO), EBSCO Host, and Biblioteca Virtual em Saúde (BVS). The keywords used were: Prevalence, Pediatric Obesity, Child Overweight, and Portugal. Results and Discussion: Data on the preva- lence of childhood obesity in Portugal are presented, describing the results of studies conducted at national and district level, in the different age groups and by sex. Conclusions: The data reveal that the prevalence of overweight in Portugal ranges between 20 and 40%, and of obesity between 10 and 15%, which reinforces the urgent need for monitoring and implementing preventive measures.